POLA DAN DOMINASI KEKUASAAN OLIGARKI LOKAL PADA INDUSTRI PERTAMBANGAN DI KALIMANTAN TIMUR - Budiman; Daswati; Muhammad Nur Alamsyah (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2025)
This study aims to uncover the patterns and dominance of local oligarchic power in the coal mining industry in East Kalimantan. Using a descriptive qualitative approach with in-depth interview techniques and documentation studies, this study traces how power is exercised through a network of political, economic, military, and social organizational actors. The findings show that oligarchic dominance occurs not only through control of economic resources, but also through the co-optation of state institutions such as the legislature, bureaucracy, security forces, and media. The power structure is hierarchical-functional, with figures such as Said Amin, Tan Paulin, Haji Andre, Haji Alex, and Ismail Bolong playing complementary roles in the extractive power ecosystem. This study concludes that local oligarchs form a new historical bloc that unites formal-informal and legal-illegal power. Dismantling this dominance requires regulatory reform, political transparency, strengthening civil society, and transformation of political ethics.